Negara (Islam) Modern Vs Pemerintahan Islam; Studi Konsep Wael Al-Hallaq dalam Buku The Impossible State - Moad, Edward (Jurnal Review Politik, 2015)
This paper deals with Wael Hallaq’s book, The Impossible State, published by Columbia University Press, 2013. By analysing of various Islamic political analysts, like Lama Abu Odeh, Andrew March, Carl Schmitt and John Gray, the author critiques it. Wael Hallaq has studied of the 'Islamic State', which was considered in the standard of a modern state, and he described as "impossible and contradictory". This statement was an assessment that refers to the modern state on the one hand, and which is referred by Hallaq as 'Islamic government' on the other hand. Through historical analysis, the authors noticed that history has become a battleground in which the conflict between Islam and the state took place in the area of subjectivity. In this case, history was understood as a contradiction between two opposing historical relationship in one trencendency.